Bimetallic Fe–Cu/beta zeolite catalysts for direct hydroxylation of benzene to phenol: effect of the sequence of ion exchange for Fe and Cu cations. Issue 20 (7th September 2020) - Xiao, Peipei; Osuga, Ryota; Wang, Yong; Kondo, Junko N.; Yokoi, Toshiyuki
Abstract : Recently, bimetallic cation-exchanged zeolite catalysts have received much attention. Abstract : Recently, bimetallic cation-exchanged zeolite catalysts have received much attention. In this study, we focused on the bimetallic Fe and Cu beta zeolite, and investigated the effect of the ion-exchange sequence on the physicochemical and catalytic properties upon introducing Fe and Cu cations into beta zeolites. The bimetallic catalysts were prepared by the ion-exchange method using NH4 + -type beta in three sequences, namely, 1.) Fe followed by Cu, 2.) Cu followed by Fe, and 3.) Fe and Cu at the same time. The bimetallic Fe–Cu/beta zeolites prepared by different sequences showed different physicochemical properties and catalytic properties in the hydroxylation of benzene with H2 O2 . To clarify the reasons for this, the content and states of the metallic species were systematically characterized by ICP-AES, in situ NO adsorption FTIR spectroscopy, XPS and H2 -TPR technologies. It was indicated that the ion-exchange sequence influenced the content and the states of the Fe and Cu species, and that the metallic state had a greater influence on the catalytic properties than the content.